(untitled) (Research, Society and Development, 2022)
Objective: to know the reasons for non-attendance to prevent cervical cancer by women. Methods: descriptive study in the action research modality conducted in a municipality located in the North of the state of Minas Gerais, women registered in a Basic Health Unit who missed more than twice in the gynecological consultation were approached. Home visits were made in the area covered by the Basic Health Unit, an interview was used with a semi-structured script, and the collection of patients recorded in a specific device, the data were analyzed through content analysis. Results: seven women aged between 24 and 52 years participated in the study, the reasons for non-attendance related to structural, personal and cultural barriers. Conclusion: feelings of fear and shame, lack of information about the examination, availability of hours and lack of interest, aversion to the examination and laziness were presented as barriers by women to carry out the prevention of cervical cancer.